Involving people with dementia in developing an interactive web tool for shared decision-making: experiences with a participatory design approach. Issue 12 (5th June 2018) - Span, Marijke; Hettinga, Marike; Groen-van de Ven, Leontine; Jukema, Jan; Janssen, Ruud; Vernooij-Dassen, Myrra; Eefsting, Jan; Smits, Carolien
Abstract: Purpose: The aim of this study was at gaining insight into the participatory design approach of involving people with dementia in the development of the DecideGuide, an interactive web tool facilitating shared decision-making in their care networks. Method : An explanatory case study design was used when developing the DecideGuide . A secondary analysis focused on the data gathered from the participating people with dementia during the development stages: semi-structured interviews ( n  = 23), four focus group interviews ( n  = 18), usability tests ( n  = 3), and a field study ( n  = 4). Content analysis was applied to the data. Results : Four themes showed to be important regarding the participation experiences of involving people with dementia in research: valuable feedback on content and design of the DecideGuide, motivation to participate, perspectives of people with dementia and others about distress related to involvement, and time investment. Conclusions : People with dementia can give essential feedback and, therefore, their contribution is useful and valuable. Meaningful participation of people with dementia takes time that should be taken into account. It is important for people with dementia to be able to reciprocate the efforts others make and to feel of significance to others. Implications for Rehabilitation: People with dementia can contribute meaningfully to the content and design and their perspective is essential for developing useful and user-friendly tools. Participating in research activities may contribute to social inclusion, empowerment, and quality of life of people with dementia.